Effect of mycorrhizal inoculation on development and flowering of Tagetes patula L. ‘Yellow Boy’ and Salvia splendens Buc’hoz ex Etl. ‘Saluti Red’ - Beata Janowska; Roman Andrzejak (Acta Agrobotanica, 2017)
The effect of mycorrhization on development and flowering of Tagetes patula L. ‘Yellow Boy’ and Salvia splendens Buc’hoz ex Etl. ‘Saluti Red’ was assessed. Control treatments were those in which plants were grown in peat substrate, as opposed to the treatments in which the substrate was supplemented with mycorrhizal fungi. Mycorrhiza-treated plants of T. patula ‘Yellow Boy’ produced more inflorescence buds. In S. splendens ‘Saluti Red’, thanks to symbiosis with fungi, more flowers per inflorescence developed. Mycorrhization had no effect on plant height in T. patula ‘Yellow Boy’ and S. splendens ‘Saluti Red’. However, after its application plants tillered more intensively forming more primary lateral shoots. Mycorrhiza-treated cultivars of both species had a higher index of greenness.